Unlocking the potential of azide-phosphine Staudinger reaction for the synthesis of poly(arylene iminophosphorane)s and materials therefrom - Tomaž Kotnik; Antoine Debuigne; Julien De Winter; Matej Huš; Albin Pintar; Sebastijan Kovačič (Communications Chemistry)
Abstract Iminophosphoranes with the general formula (R3P═NR′) have great potential in synthetic chemistry as valuable precursors/intermediates in organic synthesis or as building blocks for various organic compounds. However, the synthetic approaches and conditions to prepare iminophosphoranes are still poorly understood, limiting the utility of this chemistry for organic materials. In this article, a simple and efficient synthesis of previously unattainable poly(arylene iminophosphoranes) is reported. The azide-phosphine Staudinger polycondensation is used, and the reaction conditions are carefully studied, including consideration of light and air, the influence of solvent and temperature, and investigation of the electronic and steric effects of multiazides. The newly defined reaction conditions appear to be highly versatile, allowing the use of both electron-rich and electron-deficient arylazides for reaction with phosphines to synthesize a library of poly(arylene iminophosphorane) networks that exhibit exceptional thermal and oxidative stability. Interestingly, despite the ylidic-form of the iminophosphorane linkage as shown by theoretical calculations, these newly developed poly(arylene-iminophosphorane) networks exhibit semiconducting properties, such as absorption band edges up to 800 nm and optical band gaps in the range of 1.70 to 2.40 eV. Finally, we demonstrate the broad applicability of these polymers by processing them into glassy films, creating foam-like structures and synthesizing metallo-polymer hybrids.